Is serum hemoglobin level an independent prognostic factor for IgA nephropathy?: a systematic review and meta-analysis of observational cohort studies - Kang Zhang; Meng-di Wang; Shang-shang Jiang; Long Tang; Yue-fen Wang; Yuan Meng; Zhen Cai; Xue-yan Sun; Fang-qiang Cui; Wen-jing Zhao (Renal Failure)
Background Decreased serum hemoglobin (Hb) level is associated with Immunoglobulin A nephropathy (IgAN) progression. However, whether serum Hb level is an independent prognostic factor of IgAN remains controversial. Herein, we aimed to investigate the prognostic value of serum Hb level in IgAN.Methods The Cochrane Library, Embase, PubMed and Open Grey databases were systematically searched and reviewed. Kidney disease progression of IgAN was defined as a doubling of serum creatinine (SCr), a 30% reduction in estimated glomerular filtration rate (eGFR), end-stage renal disease (ESRD), or death. We evaluated the hazard ratio (HR) between serum Hb level and the incidence of kidney disease progression in IgAN before and after adjusting for relevant covariates.Results We included nine studies with 10006 patients in the meta-analysis. As a continuous variable, we found that serum Hb was an independent prognostic factor of IgAN [unadjusted HR = 0.89, 95% confidence interval (CI) = 0.84–0.95, I2 = 98%; adjusted HR = 0.85, 95% CI = 0.79–0.91, I2 = 0%]. The sensitivity analysis confirmed the stability of these results. Consistently, as a dichotomous variable defined as the below/above cutoff for anemia, we observed a positive correlation between serum Hb and kidney disease progression in IgAN (unadjusted HR = 2.12, 95% CI = 1.44–3.12, I2 = 79%; adjusted HR = 1.65, 95% CI = 1.20–2.27, I2 = 0%).Conclusion Serum Hb level was independently correlated with the incidence of kidney disease progression in IgAN.